2021
DOI: 10.1111/vcp.13028
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal hypoglycemia and blood glucose concentrations in neonatal tropical goat kids

Abstract: Functional changes during immediate postnatal life involve metabolic, thermoregulatory, respiratory, and cardiovascular adjustments from the period of neonatal adaptation to that of physiologic maturity. 1,2 Thermoregulation in neonatal goats is generally poor at birth, and blood glucose plays a significant supportive role by supplying substrate for shivering thermogenesis to aid thermoregulation. [3][4][5] During immediate postnatal life, the newborn animal depends on brown adipose tissue as the primary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Hypoglycemia at birth has been reported in 22.5% of goat kids, but figures are significantly higher for the Sahel breed, twins, and newborns with low birth weight ( 55 ). When neonates' glucose concentrations are inadequate, they begin to consume muscular reserves through the Cori cycle.…”
Section: Anatomical-physiological Characteristics Of Thermoregulation...mentioning
confidence: 99%
See 3 more Smart Citations
“…Hypoglycemia at birth has been reported in 22.5% of goat kids, but figures are significantly higher for the Sahel breed, twins, and newborns with low birth weight ( 55 ). When neonates' glucose concentrations are inadequate, they begin to consume muscular reserves through the Cori cycle.…”
Section: Anatomical-physiological Characteristics Of Thermoregulation...mentioning
confidence: 99%
“…This limit on glycogen storage in the liver and muscles at birth means that goat kids, lambs, and calves have low glucose concentrations that make them susceptible to hypoglycemia since those limited reserves can be depleted rapidly within the first 12 h postpartum. This effect exacerbates if the onset of feeding is delayed ( 55 ).…”
Section: Anatomical-physiological Characteristics Of Thermoregulation...mentioning
confidence: 99%
See 2 more Smart Citations
“…GLU is the main source of energy for ruminants. Studies have shown that goats have low blood sugar levels after birth and gradually increase with age 30 . In this study, goats had slightly higher blood glucose levels than D60 after birth, possibly related to the goats’ postnatal colostrum intake to maintain energy needs 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%